Delivery mechanisms of agricultural information and knowledge to smallholder farmers in Tanzania: A meta €“analysis study - Ndimbwa, Tumpe; Ndumbaro, Faraja; Mwantimwa, Kelefa (University of Dar es Salaam Library Journal, 2020)
Regardless of concerted interventions and initiatives made to foster agricultural information and knowledge delivery to smallholder farmers, access to these resources remains largely poor in rural Tanzania. To gain insights, the present study examined the delivery mechanisms of agricultural knowledge among smallholder farmers in Tanzania. The study employed a meta-analysis approach where 20 extant studies on agricultural information and knowledge in Tanzania were reviewed. During data analysis, Microsoft Excel 2010 was used to perform descriptive statistics analyses. The study ' s findings reveal that there are various sources and delivery mechanisms of agricultural information and knowledge to the smallholder farmers in Tanzania. The findings further expose that there is no consensus on channels that are most suitable for delivering these resources to rural areas. While some prior studies show mass media as predominant sources, others inform that oral information and knowledge delivery mechanism are a prime sources and channels. Besides, the study reveals that rural Tanzania is not immune to factors that constrain delivery of agricultural information and knowledge. Factors like lack of communication tools, illiteracy, irrelevance of content, packaging information using languages farmers are not conversant with, lack of power supply, and limited income limit information and knowledge delivery and access. To speed up agricultural information and knowledge penetration to smallholder farmers in rural Tanzania, farmers groups, demonstration plots, farmers ' field study tours, agricultural shows and NGOs are recommended as sources and channels.